A cause and effect relationship between FIIs, DIIs and stock market returns in India: Pre- and post-demonetization analysis - Narayan Parab; Y. V. Reddy (Future Business Journal, 2020)
In one of the most historic decisions in the Indian economy, the Government of India demonetized its two highest currency notes (Rs. 500 and Rs. 1000) on November 8, 2016. The Indian stock market does not only consist of domestic investors; however, it does attract a large pool of foreign investors. The present study, considering the significance of demonetization in Indian economy, attempted to examine the association between foreign institutional investment (FII), domestic institutional investment (DII) and stock market returns taking into account a period of 686 days from June 11, 2015, to March 27, 2018, i.e., 343 days pre- and post-demonetization. The study made use of various statistical techniques such as summary statistics, augmented Dickey-Fuller test, correlation analysis and regression analysis. The results indicate a negative relationship of FIIs and DIIs with Nifty 50 Index Returns prior to demonetization; however, such a relationship was noticed to be positive post-demonetization. The present study did not evidence a significant impact of demonetization on FIIs and DIIs, but a significant negative impact was noticed in the case of Nifty 50 Index and various sectoral indices post-demonetization. Nifty Realty sector was found to be severely affected because of demonetization. The study will help the government in understanding the impact of demonetization on foreign and domestic institutional investors, various sectoral indices and evaluate market sentiment post-demonetization and therefore frame necessary policies. Also, the information provided in present study will help various stock market participants.
Keywords: 650; Demonetization; FIIs; DIIs; Stock market returns; Augmented Dickey-Fuller test